The effect of pre-sowing seed treatment with nonionic colloidal solutions of silver and copper metal nanoparticles on growth and water-retaining ability of winter wheat seedlings (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
In connection with the rapid development and implementation of nanotechnology in the agriculture, biology and medicine, investigation of biogenic metal nanoparticles is the topical subject that opens up the opportunities for their practical use. Growth is an integral indicator of the physiological state of plants. Their water-retaining ability is an informative marker of water metabolism and resistance of plants. In this regard, the effect of pre-sowing seed treatment with nonionic colloidal solutions of silver and copper nanoparticles on growth parameters and water regime in wheat seedlings (Triticum aestivum) of two varieties – Myronivska 808 and Renan was investigated. The response of wheat seedlings to the action of nanoparticles treatment was assessed by changing of the organs length and weight. It was expressed as tolerance index. Under nanoparticles action the length and weight of different parts of seedlings in both varieties found to be changed. Investigated nonionic colloidal solutions of biogenic metals nanoparticles act as stimulators of growth processes, in which the effect of silver nanoparticles on these indices was more effective. Pre-sowing seed treatment with metal nanoparticles has also positively influenced to water regime in wheat seedlings. Silver nanoparticles demonstrated a higher efficiency of preventing the water deficiency development in wheat seedlings of both varieties. It has been shown that pre-sowing seed treatment with nanoparticles of silver and copper stimulates growth and increases the water-retaining ability of the plant organism. This is the basis for further research and use of solutions of the most effective nanoparticles in biology and agriculture.
Keywords: Triticum aestivum, growth parameters, tolerance index, leaf plate area, water deficiency.